2015
DOI: 10.1007/s11760-015-0798-9
|View full text |Cite
|
Sign up to set email alerts
|

Saliency detection in MPEG and HEVC video using intra-frame and inter-frame distances

Abstract: Experimental results revealed that a Kullback-Leibler distance of 2.14 and area under the receiveroperator curve of 0.936 are achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The authors of [36] first suggested using stepwise regression in video-based intelligent systems. Since then, it has been effectively employed in many vision-based applications, as documented in several works, including [12,37,38].…”
Section: Reducing the Feature Spacementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [36] first suggested using stepwise regression in video-based intelligent systems. Since then, it has been effectively employed in many vision-based applications, as documented in several works, including [12,37,38].…”
Section: Reducing the Feature Spacementioning
confidence: 99%
“…This work aims to leverage the useful information encapsulated by HEVC coding in the video bitstream. HEVC bitstream information in the form of features was proven to be useful in several applications, such as static video summarization [8], encoding speedup and video transcoding [9], data embedding [10], the detection of double and triple compression [11], and saliency detection [12].…”
Section: Introductionmentioning
confidence: 99%
“…We modified the coder to generate low-level features, as described in the next section. HEVC features have been successfully used in many applications, including encoding speedup [35], video transcoding [35], data embedding [36], double and triple compression detection [37] and saliency detection [38]. Eventually, all the feature variables are added to the .h5 files of the OVP and VSUMM, as illustrated in Fig.…”
Section: Table II Proposed Hevc Feature Set Per Frame a Custom Hevc D...mentioning
confidence: 99%
“…The use of stepwise regression in video-based intelligent systems was first proposed by the authors in [41]. Since then, it was successfully used with video codec as reported in [38], [42] and [43] to mention a few. In this work, we propose the use of stepwise regression to reduce the dimensionality of both HEVC and CNNs features, in which we treat the feature variables as predictors and the class labels as response variables.…”
Section: B Proposed Stepwise Regression Solutionmentioning
confidence: 99%
“…Chen [23] designed a visual defect detection method based on multispectral deep CNN, wherein the CNN model explores surface defect information in images of different spectral bands with enhanced recognition abilities for complex texture background and defect features. Several other efforts have also been reported in the literature, such as a deep learning-based classification pipeline structure [24] introduced to perform preprocessing (e.g., distortion correction, segmentation, and perspective correction on electro-luminescence images), a deep CNN designed for solar cell surface defect classification, and an investigation on the influence of a few oversamples and increase in data on system accuracy [25].…”
Section: Introductionmentioning
confidence: 99%